A novel prosthetic knee joint with a parallel spring and damping mechanism. (12th July 2016) - Fu, Huiqun; Zhang, Xiufeng; Wang, Xitai; Yang, Rong; Li, Jian; Wang, Li; Zhang, Ning; Li, Guanglin; Liu, Tao; Fan, Bingfei; Inoue, Yoshio
Prosthetic knee joint (PKJ) is an important apparatus for trans-femoral amputees to regain walking ability. This study has two objectives: (1) to design a high performance and low-cost passive PKJ and (2) to evaluate the performance of the PKJ. In the proposed PKJ design, a four-bar linkage was employed as the mechanical structure, and parallel spring and damper were used as the two connecting rods of the four-bar linkage. With the parallel spring, the length of the connecting rod is variable and a buffer flexion angle can be generated, which was consistent with that of the human knee joint. The damper was used to regulate the swing speed of the shank. Through theoretical analysis, modeling, and simulation, key parameters of the mechanical structure were optimized. Finally, experimental studies were conducted to test the performance of the PKJ, including fatigue test and gait analysis. The results showed that the designed PKJ is reliable and the gait of PKJ is close to the healthy subject. Moreover, it is comfortable and showed no adverse effects on the amputee during the walking experiment.